Condiciones internas y externas para el Desarrollo Socioeconómico de Encarnación (Journal on studies and research of academic knowledge, 2010)
This paper begins to represent the National University of Itapúa, at the “III Latin American Symposium on International Trade, Development and Integration” but subsequently has undergone changes and additions. It is based on the paradigm of modernization theory and globalization.It tries to describe some public policies that can be applied by the municipal government, in addition to exposing the product to be industrialized in the short term to generate more local work force.It also presents some necessary conditions that must exist in the country to contribute to the industrialization process of the local and national economy, whether by local entrepreneurs, domestic or foreign.The context in which research is conducted due to the rapid development of local infrastructure, that it is not accompanied by the process of industrialization of the city,or the society evolution.
Keywords: Modernization; Society; Infrastructure; Industrialization; Traditional